Physical Condition of Students (GRADES 1-2) in Primary Schools in Hanoi City - Bien, Ly Quoc (International Journal of Humanities and Education Development (IJHED), 2025)
This study aims to assess the physical status of primary school students from grades 1 to 2 in Hanoi, focusing on anthropometric indicators and basic motor skills. Using a combination of actual measurement and survey methods, the study collected data on students' height, weight, BMI, strength, endurance, and flexibility. The results showed apparent differences between age groups and genders, with many students not achieving optimal physical development. This suggests appropriate physical education programs and a balanced diet to support children's comprehensive development.